2020
DOI: 10.12669/pjms.36.6.2337
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Levamisole in children with Frequent Relapsing and Steroid Dependent Nephrotic Syndrome at Tertiary Care Center-Karachi

Abstract: Objectives: To determine the effectiveness of levamisole in maintaining remission of proteinuria in children with frequent relapsing and steroid dependent nephrotic syndrome (FR/SDNS). Methods: This observational study on 81 children with FR /SDNS was carried out from June 2007 - June 2017 at The Kidney Center-Postgraduate Training Institute, Karachi-Pakistan. Levamisole (leva) along with low dose prednisolone on alternate day (AD) was used after induction of remission with daily oral prednisolone in chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Most other recent studies used doses of 2-3 mg/kg on alternate days for 6-24 months. Some observational studies have used doses of 2-2.5 mg/kg daily for 4-24 months [143][144][145][146][147][148][149] with three studies [147][148][149] suggesting reductions in relapse rates in patients who had not responded to alternate-day LEV. These data require further larger RCTs, powered to detect a difference, if any, for confirmation.…”
Section: Levamisolementioning
confidence: 99%
“…Most other recent studies used doses of 2-3 mg/kg on alternate days for 6-24 months. Some observational studies have used doses of 2-2.5 mg/kg daily for 4-24 months [143][144][145][146][147][148][149] with three studies [147][148][149] suggesting reductions in relapse rates in patients who had not responded to alternate-day LEV. These data require further larger RCTs, powered to detect a difference, if any, for confirmation.…”
Section: Levamisolementioning
confidence: 99%
“…Moorani et al, found fever (86.7%), cough (46.7%), urinary symptoms (20%), vomiting (13.3%), diarrhea (11.7%), abdominal pain(6.7%) and dehydration (3.3%). 6 Mahvish et al, found fever (64.9%), chills/rigor (18.9%), abdominal pain (32.4%), diarrhea and/or vomiting (13.5%), urinary symptoms (dysuria, increased frequency) (24.3%), respiratory symptoms (cough and/or breathing difficulty) (32.4%), shock (8.1%) and hypotension (10.8%). 13 In our study severe ascites was found in 34 (77.3%) cases and not severe ascites was in 10 (22.7) cases.…”
Section: Discussionmentioning
confidence: 98%
“…Relapses in steroid sensitive Nephrotic Syndrome often follow infections of upper airway or gastrointestinal tract. 6 An abnormality in the functions of the T lymphocytes and in particular the suppressor T…”
Section: Introductionmentioning
confidence: 99%
“…Univariate logistic regression was used to obtain the odds of severe disease. Factors used in logistic regression were age (children <5 years particularly), low serum albumin (found to be a predictive factor in a previous study), gender, the commonest serotype observed, presence of more than two immunosuppressive agents (presumed higher risk) and initial episode (versus relapses; in view of significant proportion of children with onset of NS and PnI) [7,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of pneumococcal infections being a trigger for the onset of NS may be more than speculation, akin to novel coronavirus (SARS CoV2) reportedly triggering various glomerular diseases [18,19,22,25,26]. Respiratory tract infections were observed to be the commonest infections in children at the onset of NS and a few reports mention identification of S. pneumoniae as the culprit organism [13,27,28]. Infections are also known to be a significant risk factor for acute kidney injury in children with NS; however, it was not commonly observed and was not explored in this study [29].…”
Section: Discussionmentioning
confidence: 99%